Augmenting Blockchain With Competition Law for a Sustainable Economic Evolution - Yawar, Syed Mohammad; Shaw, Rahul (Frontiers in Blockchain, 2022)
Since its introduction, blockchain technology has been revered, ridiculed, dismissed, embraced, and presently has become too large to ignore, witnessing exponential growth. The obvious indicator of this growth is that research revolving around blockchain technology has already raised competition in the form of directed acyclic graphs and hashgraph, all of which fall under the umbrella of distributed ledger technology (DLT). Segueing on the back of visibly positive effects of competition, we arrive at the essence of our paper. We show that the current competition regimes around the world are inefficient at promoting and maintaining competition around the world, dominated by the behemoth technology enterprises that have successfully monopolized and monetized data, which is indubitably, one of the most important assets in today’s digital age. Data gathered from users fuels the algorithms, machine learning, and artificial intelligence programs employed by these tech giants, which further entrenches their monopolistic hold over cyberspace. Blockchain and DLTs, just like any other technology, pose new threats to the competition law regimes, while also allowing the authorities to utilize the technology themselves to explore new horizons involving smart contracts, Decentralized Autonomous Organizations (DAOs), Web 3.0, and enforce competition more effectively. In our paper, we briefly illustrate the challenges presented before the competition authorities by the assimilation of blockchain in the existing establishments, and how the competition authorities can themselves collude with blockchain stakeholders to take a holistic approach and establish a symbiotic relationship, which ensures that both, survive, prosper, and enhance consumer welfare.